2017
DOI: 10.1111/vop.12509
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal thickness measurements using ultrasound pachymetry, ultrasound biomicroscopy, and digital caliper in frozen canine corneas

Abstract: The purpose of this study was to evaluate the clinical efficacy among ultrasound pachymetry (UP), ultrasound biomicroscopy (UBM), and manual measurement (MM) with digital caliper by comparing corneal thickness (COT) values obtained on frozen canine corneas ex vivo. The COT was measured using UP, UBM, and MM in 8 enucleated normal canine eyes frozen at -20℃ for 4 weeks. After thawing at room temperature for 2 hrs, the COT values were obtained from five sites in each cornea: central corneal thickness (CCOT), thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…This differs from a recent report in dogs in which the two techniques were found to produce similar central corneal thickness measurements with strong agreement between methods 21 . Another study that compared ultrasonic pachymetry to UBM in the assessment of corneal thickness of frozen canine corneas indicated that UBM consistently resulted in greater corneal thickness measurements 22 . As previously discussed, the accuracy of ultrasonic pachymetry in determination of corneal thickness is dependent upon the set velocity of the instrument being consistent with the speed of sound through the measured tissue 23 …”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This differs from a recent report in dogs in which the two techniques were found to produce similar central corneal thickness measurements with strong agreement between methods 21 . Another study that compared ultrasonic pachymetry to UBM in the assessment of corneal thickness of frozen canine corneas indicated that UBM consistently resulted in greater corneal thickness measurements 22 . As previously discussed, the accuracy of ultrasonic pachymetry in determination of corneal thickness is dependent upon the set velocity of the instrument being consistent with the speed of sound through the measured tissue 23 …”
Section: Discussioncontrasting
confidence: 94%
“…21 Another study that compared ultrasonic pachymetry to UBM in the assessment of corneal thickness of frozen canine corneas indicated that UBM consistently resulted in greater corneal thickness measurements. 22 As previously discussed, the accuracy of ultrasonic pachymetry in determination of corneal thickness is dependent upon the set velocity of the instrument being consistent with the speed of sound through the measured tissue. 23 The widely used velocity of 1640 m/s for ultrasonic pachymetry is appropriate for the human cornea, though the speed of sound in both the canine and bovine cornea has been demonstrated to be less than this, and it is likely that the same is true for the horse.…”
Section: Discussionmentioning
confidence: 79%
“…Ultrasonic pachymeters calculate CCT by measuring the length of time for an ultrasonic wave to pass through the cornea and reflect back to the transducer. Ultrasound pachymetry produces similar accuracy to optical coherence tomography (OCT) and is commonly used in veterinary ophthalmology due to affordability and ease of use 16–19 . Optical coherence tomography, although the most accurate means of gathering CCT data, is rarely used outside of an academic or research setting in veterinary medicine 20–22 .…”
Section: Introductionmentioning
confidence: 99%